Sperm whale ship strikes in the Pelagos Sanctuary and adjacent waters: assessing and mapping collision risks in summer - Di-Meglio, Nathalie; David, Lea; Monestiez, Pascal (J. Cetacean Res. Manage., 2023)
Collisions with large vessels potentially present a major conservation issue for sperm whales in the Pelagos Sanctuary in the northwestern Mediterranean Sea. The exact numbers and locations of ship strikes remain largely unknown at present. In this study, sightings of sperm whales in summer (June–September) were gathered for the period between 1998 and 2008 from nine French and Italian organisations, together covering an area of more than 68,000km. Working on a regular grid of 0.1° × 0.1° latitude/longitude cells, approximate surface density of the whales was calculated using kriging methods. A database of shipping lanes of ferries and merchant vessels was assembled, and traffic density was mapped (kilometres travelled per cell). The data was overlayed and multiplied, using ArcGis, to create a relative density surface map of sperm whales correlated with the relative density of maritime traffic. Several maps of collision risk were drawn up according to the speed class of the vessels. Of living animals that had been photo-identified, 9% had scars attributed to ship strike. Results show that sperm whales are at high risk from merchant vessels along the French and Italian continental coasts and at risk from conventional ferries on the east side of the islands of Corsica and Sardinia. It was calculated that 74 animals could be in a ship strike risk situation during the summer period in the Pelagos Sanctuary. Based on these results, mitigation measures already in place were reviewed and new measures to reduce ship strike risk are suggested.